The Influence of Palatable Diets in Reward System Activation: A Mini Review - Isabel Cristina de Macedo; Joice Soares de Freitas; Iraci Lucena da Silva Torres (Advances in Pharmacological Sciences)
The changes in eating patterns that have occurred in recent decades are an important cause of obesity. Food intake and energy expenditure are controlled by a complex neural system involving the hypothalamic centers and peripheral satiety system (gastrointestinal and pancreatic hormones). Highly palatable and caloric food disrupts appetite regulation; however, palatable foods induce pleasure and reward. The cafeteria diet is such a palatable diet and has been shown consistently to increase body weight and induce hyperplasia in animal obesity models. Moreover, palatable high-fat foods (such as those of the cafeteria diet) can induce addiction-like deficits in brain reward function and are considered to be an important source of motivation that might drive overeating and contribute to the development of obesity. The mechanism of neural adaptation triggered by palatable foods is similar to those that have been reported for nondrug addictions and long-term drug use. Thus, this review attempts to describe the potential mechanisms that might lead to highly palatable diets, such as the cafeteria diet, triggering addiction, or compulsion through the reward system.